Prevalence of mechanical low back pain among bus drivers in cairo transport authority in Egypt : Survey study - Ismail Mohamed Ismail Ibrahim; Hamed Mohamed Elkhozamy; Salwa Fadl Abdalmegeed (Cairo : Ismail Mohamed Ismail Ibrahim, 2019)
Background: Mechanical low back pain MLBP) is an impacting musculoskeletal disorder and this population is at a high risk of suffering from LBB. Purposes: to acquire lifetime, MLBP among bus drivers who are currently working at Cairo Transport Authority (CTA), as well as factors related to the workplace or the individual, and MLBP characteristics. Methods: A specifically designed questionnaire was distributed to the bus drivers who are currently working in CTA (574 bus drivers). Results: all the bus drivers have completed the questionnaire. The lifetime prevalence of MLBP was 72.3% (95% CI from 69.5% to 76.8%), most prevalent bus drivers with MLBP were driving Emarat type bus (52.3%). Conclusion: Mechanical low back pain is common among Egyptian bus drivers at the prevalence, making Cairo Transport Authority a high-risk group, which necessitate appropriate intervention to manage such sequelae
Thesis (M.Sc.) - Cairo University - Faculty of Physical Therapy - Department of Musculoskeletal Disorder
Issued also as CD
Keywords: Bus Drivers; Low Back Pain; Prevalence